Correlation between the cadmium, calcium and potassium in the body and indices of cardiovascular system of athletes - O.A. Reshetniak (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Performed a functional examination of the cardiovascular system in 80 students (40 players, 40 students are not involved in sports). Used the method of electrocardiography and computer rheography. The study was conducted in a state of physiological rest during exercise and during the recovery period. The level of chemical elements in the hair was determined by X-ray fluorescence analysis. The element of balance of athletes showed that the elemental balance of athletes in terms of the built environment is more satisfactory than the students. Students have a shortage of essential items. The study features of response of the cardiovascular system to exercise physiological significance of cadmium found in athletes. Character correlations essential elements with indices cardiovascular system conform to their known roles in physiological processes at the cellular level.